2003
DOI: 10.1016/s0960-9822(03)00083-6
|View full text |Cite
|
Sign up to set email alerts
|

The JNK Cascade as a Biochemical Switch in Mammalian Cells

Abstract: JNK proteins are ubiquitously expressed, evolutionarily conserved MAP kinases that are involved in stress responses. Recently, it was shown that the JNK cascade in Xenopus oocytes exhibits sustained, all-or-none responses to graded, transient stimuli. Here, we have examined the character of the JNK cascade's response in mammalian cells. The steady-state responses of JNK to sorbitol and anisomycin were found to be highly ultrasensitive in HeLa cells, HEK 293 cells, and Jurkat T cells. The JNK responses were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
103
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 24 publications
9
103
1
Order By: Relevance
“…Importantly, such feedback-based switches can generate bistability; i.e., the occurrence of two distinct subpopulations that exhibit different phenotypes within the isogenic population (2). Maturation in developing oocytes in Xenopus embryos is governed by a bistable switch, and the Hedgehog network, responsible for cellular differentiation in a diversity of eukaryotes, involves bistable switching as well (3,4). These types of regulatory switches are also found in single-celled organisms such as yeasts and bacteria, where they lead to phenotypic variability within the isogenic population (2).…”
mentioning
confidence: 77%
“…Importantly, such feedback-based switches can generate bistability; i.e., the occurrence of two distinct subpopulations that exhibit different phenotypes within the isogenic population (2). Maturation in developing oocytes in Xenopus embryos is governed by a bistable switch, and the Hedgehog network, responsible for cellular differentiation in a diversity of eukaryotes, involves bistable switching as well (3,4). These types of regulatory switches are also found in single-celled organisms such as yeasts and bacteria, where they lead to phenotypic variability within the isogenic population (2).…”
mentioning
confidence: 77%
“…The kinetics of MAP-kinase signaling has been studied in great detail by Ferrell (Bagowski et al, 2003), who has shown convincingly that this signaltransduction pathway functions as a bistable switch in frog eggs. According to Ferrell's evidence, the switch is created by a positive-feedback loop superimposed on a highly nonlinear (sigmoidal) signal-response curve of the kinase cascade (Ferrell and Machleder, 1998;Ferrell, 2002).…”
Section: Early and Delayed-response Genesmentioning
confidence: 99%
“…It has been suggested that a high level of JNK activity may induce the degeneration of unhealthy oocytes (17). However, this suggestion cannot explain the functions of maternal JNK signaling in healthy Xenopus embryos (18).…”
mentioning
confidence: 99%